NICER detection of pulsations from RX J0529.8-6556 - Vasilopoulos, G.; Jaisawal, G. K.; Treiber, H.; Ray, P. S.; Haberl, F.; Bailyn, C.; Gendreau, K. (The Astronomer's Telegram, 2020)
Following the SRG/eROSITA discovery of a strong outburst from the LMC Be/X-ray binary RX J0529.8-6556 (Haberl et al., ATEL #13828) we triggered NICER ToO observations to search for pulsations and obtain high-quality spectra.
Keywords: Binary; Neutron Star; Pulsar; Request for Observations; Transient